Distribution of bacterial communities across plateau freshwater lake and upslope soils - Chen, Yihui; Dai, Yu; Yilin Wang; Wu, Zhen; Xie, Shuguang; Yong Liu (JOURNAL OF ENVIRONMENTAL SCIENCES, 2016)
Microorganisms are involved in a variety of biogeochemical processes in natural environments. The differences between bacterial communities in freshwaters and upslope soils remain unclear. The present study investigated the bacterial distribution in a plateau freshwater lake, Erhai Lake (southwestern China), and its upslope soils. Illumina MiSeq sequencing illustrated high bacterial diversity in lake sediments and soils. Sediment and soil bacterial communities were mainly composed of Proteobacteria, Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi and Planctomycetes. However, a distinctive difference in bacterial community structure was found between soil and sediment ecosystems. Water content, nitrogen and pH affected the distribution of the bacterial community across Erhai Lake and its upslope soils. Moreover, the soil bacterial community might also be shaped by plant types. This work could provide some new insights into plateau aquatic and terrestrial microbial ecology. (C) 2015 The Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences. Published by Elsevier B.V.